King James, the First: Dæmonologie (1597). - James I, King of England (London, John Lane; New York, E. P. Dutton & company, 1924)
81, 29 p. 19 cm; "This reprint first published in 1924."; Newes from Scotland has been ascribed to James Carmichael, minister of Haddington. cf. Sir James Melville, Memories, p. 195, and D. Webster, Collection of tracts on witchcraft, etc., 1820, p. 38
Keywords: Fian, John, -1591